Answer:
see explanation
Step-by-step explanation:
5x² + 5x + 3 = 0 ← in standard form
with a = 5 , b = 5 , c = 3
Solve using the quadratic formula
x = [tex]\frac{-b+/-\sqrt{b^2-4ac} }{2a}[/tex]
= [tex]\frac{-5+/-\sqrt{5^2-(4(5)(3)} }{2(5)}[/tex]
= [tex]\frac{-5+/-\sqrt{25-60} }{10}[/tex]
= [tex]\frac{-5+/-\sqrt{-35} }{10}[/tex]
= [tex]\frac{-5+/-\sqrt{-1(35)} }{10}[/tex]
= [tex]\frac{-5+/-i\sqrt{35} }{10}[/tex]
Then
x = [tex]\frac{-5}{10}[/tex] ± [tex]\frac{1}{10}[/tex] i[tex]\sqrt{35}[/tex] , that is
x = - [tex]\frac{1}{2}[/tex] - [tex]\sqrt{x} \frac{1}{10}[/tex] i[tex]\sqrt{35}[/tex] , - [tex]\frac{1}{2}[/tex] + [tex]\frac{1}{10}[/tex] i[tex]\sqrt{35}[/tex]